O Plano Nacional de Educação: desafios a partir da construção do Plano Municipal de Educação de Uberlândia - Jorgetânia da Silva Ferreira; Marina Ferreira de Souza Antunes; Olenir Maria Mendes (EccoS – Revista Científica)
This article aims to describe and analyze the preparation process of the Municipal Education Plan for the city of Uberlândia (MG), in conformity with the forecast of the National Education Plan. It discusses the process of preparing the National Education Plans, contextualizing it historically. The preparation of the Municipal Education Plans has been the great challenge to be faced by the educational policies,in this way, this paper presents some aspects of the preparation of the Plan which is being built in Uberlândia. It emphasizes democratic participation as the possibility of building a plan, indicating the challenges and controversies of a collective elaboration of a Municipal Education Plan.